Control of Microcystis (Cyanobacteria) using the fruit of Macleaya cordata: from laboratory experiment to in situ field test. Issue 4 (1st July 2017) - Zhang, Huiling; Chen, Anwei; Li, Jinlong; Liu, Deming; Shao, Jihai
Abstract: Biologically derived algicidal substances are regarded as environmentally friendly in the control of harmful cyanobacterial blooms. To evaluate the possible control of Microcystis- based water blooms using fruit from Macleaya cordata (MC-fruit), the effects of MC-fruit on the growth, polyphasic chlorophyll fluorescence transients, microcystin production and efficacy of in situ cyanobacterial bloom removal were investigated. The results showed that MC-fruit could effectively inhibit the growth of M. aeruginosa PCC7806 at a concentration of 1 mg l −1 . MC-fruit stress caused severe damage to photosynthesis of M. aeruginosa and decreased the content of cellular microcystin-LR. The results of an in situ field test showed that MC-fruit effectively reduced the biomass of Microcystis and improved water quality. Accordingly, MC-fruit may be a useful biologically derived algicide for cyanobacterial bloom control.